Depolymerization of lignin by microwave-assisted methylation of benzylic alcohols. (October 2016) - Zhu, Guodian; Qiu, Xueqing; Zhao, Ying; Qian, Yong; Pang, Yuxia; Ouyang, Xinping
Graphical abstract: Highlights: A new two-step lignin depolymerization strategy was proposed. Methylation of benzylic alcohols was achieved efficiently and selectively under microwave irradiation. Methylation of benzylic alcohols dramatically increased the reactivity of β O4 bond cleavage and the products selectivity. Methylation pretreatment facilitated lignin depolymerization to produce aromatic monomers. Methylation pretreatment reduced the oxygen content of depolymerized aromatic monomers. Abstract: A new two-step lignin depolymerization strategy was developed, in which the benzylic alcohols in lignin was methylated under microwave irradiation, followed by a hydrogenolysis for the cleavage of βO4 bond with Pd/C as the catalyst. The results showed that an efficient and selective catalytic methylation of benzylic alcohols was achieved with various lignin model compounds, and the acidic environment promoted the methylation of benzylic alcohol. Methylation of benzylic alcohol increased the βO4 bond cleavage rate by 55.9%, and improved products selectivity. Preliminary study of lignin depolymerization illustrated that methylation pretreatment of benzylic alcohols facilitated lignin depolymerization to produce aromatic monomers and reduced the oxygen content of aromatic monomers.